To Be or Not to Be God—The Issue of Authorial Power in Dostoevsky - Žolkovskij, Aleksandr Konstantinovič (Religions, 2021)
This paper problematizes the now widely accepted concept of Dostoevsky’s dialogism, which alleges the ‘Author’s’ equal empowerment of all his characters. Using examples from Crime and Punishment and The Brothers Karamazov, Zholkovsky focuses on instances of ‘scene-staging’ based on the ‘scripts’ devised and enacted by some characters, that are ‘read,’ with varying success, by their targets. He documents the resulting ‘discursive combat’ among the characters, with special attention paid to those ‘playing god’ and thus, the more ‘authorial’ among them. In several cases, the would-be ‘divine’ manipulation is shown to be consistently subverted by the Dostoevskian narrative. However, in one instance, where Aliosha Karamazov charitably scripts Captain Snegirev’s behavior, the ensuing discussion of this episode, in Aliosha’s conversations with Lise Khokhlakova, upholds Aliosha’s right to play god with the Other—“for the Other’s own good”, of course (not unlike the Grand Inquisitor).